Pengaruh Kualitas Sumber Daya Manusia, Profesionalisme Kerja Dan Komitmen Terhadap Kinerja Pegawai (Studi Kasus Pada Pemerintahan Kota Malang Bagian Umum) - Moh. Syifa; Afi Rachmat Slamet; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This observasion provides performance improvement models and strategies for employees working at Malang City Hall to increase Staff performance. This study is aim to identify and analyze how human resources quality, expertise of work, and commitment simultaneously affect to the staff performance at Malang City Headquarters. This survey uses a quantitative survey method. The survey used a sample of 41 respondents, all of whom are officials of the Government-General of Korea. This study used the multiple linear regression method is the analytical method used in and the hypothesis test using SPSS software. The research finding are as follows: (1) Staff quality, work expertise, and commitment also have a significant effect on staff performance. (2) The quality of personnel has a positive effect on staff performance, but it is not significant. (3) Work professionalism have a significant effect on staff performance. (4) Commitment can have a significant effect on staff performance. Keywords: Human Resource Quality, Work Professionalism, Commitment, Staff Performance.